2020
DOI: 10.2337/db20-0204
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes in Islets of Langerhans Preceding the Onset of Diabetes

Abstract: The identification of individuals with a high risk of developing type 2 diabetes (T2D) is fundamental for prevention. Here, we used a translational approach and prediction criteria to identify changes in DNA methylation visible before the development of T2D. Islets of Langerhans were isolated from genetically identical 10-week-old female New Zealand Obese mice, which differ in their degree of hyperglycemia and in liver fat content. The application of a semiexplorative approach identified 497 differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 49 publications
0
36
0
1
Order By: Relevance
“…Other variants in the TENM2 gene were associated with multiple traits including smoking status (p=1.6×10 -17 ) and BMI (p=2.6×10 -8 ) in the UK Biobank. Furthermore, it was previously reported that the DNA methylation status in TENM2 is among the strongest predictors of incident type 2 diabetes 46 .…”
Section: Discussionmentioning
confidence: 96%
“…Other variants in the TENM2 gene were associated with multiple traits including smoking status (p=1.6×10 -17 ) and BMI (p=2.6×10 -8 ) in the UK Biobank. Furthermore, it was previously reported that the DNA methylation status in TENM2 is among the strongest predictors of incident type 2 diabetes 46 .…”
Section: Discussionmentioning
confidence: 96%
“…For each group (B6‐ ob/ob and NZO), five samples (each containing islets of one to two mice) were sequenced by GATC (Konstanz, Germany) on an Illumina HiSeq platform. Quality control and bioinformatic analysis were described previously 43 . Only transcripts with an absolute fold change >0.7 were considered for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Quality control and bioinformatic analysis were described previously. 43 Only transcripts with an absolute fold change >0.7 were considered for further analysis. KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis was performed using the David data base tool 7, 44 with cut-off fold enrichment set to >1.7 and enriched P value <.05.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…In fact, such epigenetic changes can occur preceding T2D, as illustrated by a recent study in diabetic mice, that identified DNA methylation changes associated with differential expression of several genes. Notably, the differentially methylated and expressed genes were enriched in pathways associated with insulin secretion (161). Similarly, islets from obese mice show an upregulation of Dnmt3a, which leads to increased Nkx6.1 promoter methylation, reduced Nkx6.1 and insulin expression, and consequently, impaired islet function (162).…”
Section: Dysregulation Of Islet Dna Methylation Landscape In Diabetesmentioning
confidence: 99%